The Influence of the Montessori Approach on Mathematical Problem-Solving Skills Among Fourth-Grade Elementary Students - Hidayat, Resti Resti; Supriadi, Supriadi; Hendriawan, Dedi; Fajriani, Putri (Universitas Negeri Makassar, 2025)
Problem-solving ability is a higher-order thinking skill essential to develop from the elementary school level. However, mathematics instruction in elementary schools remains predominantly conventional and has not yet optimally fostered students' critical thinking and systematic problem-solving skills. This study aims to analyze the effect of the Montessori approach on the mathematical problem-solving abilities of fourth-grade elementary students. This research employed a quantitative approach with a quasi-experimental design, specifically a non-equivalent control group pretest-post test design. The sample consisted of 60 students, divided into 30 students in the experimental group and 30 in the control group. The results of the paired sample t-test indicated a significant improvement in the experimental group, with a mean pretest score of 20.3 and a post-test score of 30.7, along with a significant value of 0.000 (p < 0.05). Furthermore, the Mann–Whitney U test on the gain scores yielded a significance value of 0.000, demonstrating a statistically significant difference in the improvement of problem-solving abilities between the experimental and control groups. The findings confirm that the Montessori approach is effective in enhancing students' problem-solving skills in mathematics learning.